Considerations for using the 4 mm Plate Geometry in the Dynamic Shear Rheometer for Low Temperature Evaluation of Asphalt Binders. Issue 11 (November 2019) - Hajj, Ramez; Filonzi, Angelo; Rahman, Syeda; Bhasin, Amit
The low-temperature properties of asphalt binder have attracted attention in recent years thanks to an increase in the use of reclaimed asphalt pavements (RAP). Traditional methods to evaluate the low-temperature properties of the binder require a large amount of binder that needs to be recovered from RAP samples for testing with a Bending Beam Rheometer (BBR). To economize on sample size for RAP materials and also for emulsion residues, previous researchers have explored the potential of using a 4 mm diameter specimen with a Dynamic Shear Rheometer (DSR) in lieu of the BBR. To compare results from frequency sweep tests conducted using the DSR with results from the BBR, data from the former need to be converted to time domain and subsequently from a shear load response to an axial load response. Previous research studies have developed methods to accomplish these two conversions to compare data from the DSR with data from the BBR. The objective of this study is to examine some of these methods from the literature and elsewhere based on the principles of linear viscoelastic interconversion using a set of 11 different binders. Results using different analytical approaches from this study show that the DSR has good repeatability and verify that it can be used as a surrogate for the BBR to determine low-temperature properties, while exercising some caution with some of the assumptions related to Poisson's ratio.